Comparative Characterization of Rep Proteins from the Helper-Dependent Adeno-Associated Virus Type 2 and the Autonomous Goose Parvovirus - Smith, Deborah H. (American Society for Microbiology, 1999)
Adeno-associated viruses (AAVs) are nonautonomous human parvoviruses in that they are dependent on helper functions supplied by other viruses or on genotoxic stimuli for conditions permissive for replication. In the absence of helper, AAV type 2 enters latency by integration into a specific site on human chromosome 19. This feature of AAV, in combination with a lack of pathogenicity, makes AAV an attractive candidate vector for human gene therapy. Goose parvovirus (GPV) is both autonomous and pathogenic yet is highly homologous to AAV. To address the molecular bases for the different viral lifestyles, we compare the AAV and GPV nonstructural proteins, Rep78 and Rep1, respectively. We find that Rep78 and Rep1 possess several biochemical activities in common, including (i) high-affinity DNA binding for sequences that constitute the minimal DNA replication origin; (ii) nucleoside triphosphate-dependent DNA helicase activity; and (iii) origin-specific replication of double-stranded linear DNA. These experiments also establish a specific 38-bp DNA sequence as the minimal GPV DNA replication origin. It is noteworthy that although the proposed Rep binding sites of GPV and AAV are highly similar, Rep1 and Rep78 show a high degree of specificity for their respective origins, in both binding and replication assays. One significant difference was observed; with the minimal replication origin in adenovirus-uninfected extracts, Rep78-mediated replication exhibited low processivity, as previously reported. In contrast, Rep1 efficiently replicated full-length template. Overall, our studies indicate that GPV Rep1 and AAV Rep78 support a comparable mode of replication. Thus, a comparison of the two proteins provides a model system with which to determine the contribution of Rep in the regulation of dependence and autonomy at the level of DNA replication.